The Influence Analysis of Organizational Culture and Motivation of The Caddy Work Satisfaction In A. Yani Golf Surabaya - Noerchoidah; Sumadji Harryono (Journal of Economy, Accounting and Management Science (JEAMS), 2019)
This study aims to determine the relationship between organizational culture and motivation with job satisfaction. There are two variables that function as independent variables, namely the culture of motivation and motivation. Job satisfaction function as the dependent variable in this study. The hypothesis proposed in this study is divided into one main hypothesis, namely the correlation between organizational culture and motivation with job satisfaction. Two minor hypotheses proposed in this study are a positive correlation between organizational culture and job satisfaction, and a positive correlation between motivation and job satisfaction. The sample of this study was the caddy of Yani Golf Surabaya, which were obtained by random sampling technique. Data were collected through a questionnaire method and analyzed by regression methods. The results of this study indicate that there is a significant relationship between organizational culture and motivation with job satisfaction, while the dominant independent variable and cultural variables are the main contributors in influencing job satisfaction. This research also shows that there is a positive and significant correlation between organizational culture and job satisfaction, where continuous and normative factors become dominant. This research also proves that there is a significant relationship between motivation and job satisfaction. The dominant factor is organizational suitability and clarity.